4-Lump kinetic model of the co-pyrolysis of LDPE and a heavy petroleum fraction. (15th February 2020) - Schubert, Teresa; Lechleitner, Andreas; Lehner, Markus; Hofer, Wolfgang
Abstract: Pyrolysis of post-consumer plastics is a promising strategy to recover valuable hydrocarbons from waste streams. In this study, the lumping approach is adopted to model the kinetics of a continuous co-pyrolysis process for low-density polyethylene (LDPE) and a heavy petroleum residue fraction (HPR). All evolving species are merged in four lumps based on their boiling range: residue (R, >410 °C), spindle oil (SO, 350–410 °C), light liquids (LL, IBP – 350 °C) and gas (G, noncondensable at 0 °C). The experimental results of a tubular laboratory cracker with a mixture of LDPE and HPR at different reactor lengths between 19.4 and 33 m provide data to estimate kinetic parameters for all six considered reactions and the overall reaction enthalpy. Based on the rate equations for irreversible, monomolecular, first-order reactions and the mass and heat balance of an incrementally modeled tubular reactor, a MATLAB algorithm solves the optimization problem including a bottom-up approach to find suitable initial values. The calculated frequency factors vary over a wide range from 10 2 to 10 8 s −1 and the obtained activation energies are between 147 and 313 kJ mol −1 . The determined value for the overall reaction enthalpy is 4669 kJ mol −1 . The results of the modeled system are in good agreement with experimental yields and can be implemented into a process model of the LDPE-HPR co-pyrolysis for simulation and optimization purposes.